If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3x + -2x + 5 = 0 Reorder the terms: 5 + 3x + 3x + -2x = 0 Combine like terms: 3x + 3x = 6x 5 + 6x + -2x = 0 Combine like terms: 6x + -2x = 4x 5 + 4x = 0 Solving 5 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = 0 + -5 4x = 0 + -5 Combine like terms: 0 + -5 = -5 4x = -5 Divide each side by '4'. x = -1.25 Simplifying x = -1.25
| 5v^2-7v=0 | | s^2+24s=0 | | x^2-12x+36=90 | | 0.6+4.8=1.5 | | x-12x+4=9 | | -9x-15/6=11 | | 6-x+5-5=-1+x | | -8(6x-6)=-240 | | -576=-8(6x+6) | | 2x+6(-3x-4)=136 | | -6x+2(5x+13)=54 | | 3x^2-2y=0 | | 6a^2b-11a^2b=0 | | 178=-4x-7(-2x-14) | | x+17=3x+3 | | 178=-4x-7(-2-14) | | 6m+8=9m+29 | | 3x^2-3x+1= | | a(2a+3)-2(3a-5)= | | x^2+0.3x-1.8= | | x^2-2.6x+1.6= | | -4m+1=(7m+5)/5 | | 2*18-7=29 | | x^2-441y^2= | | 2x+8+5=x-2x+8 | | 2x+10-6=6x-6+12 | | 3-(x-4)=5 | | p(x)=x^2+4x-12 | | 2x+8-5=-7 | | 2(x+4)-5=-7 | | 9x-14=31 | | 6,4-5x=2 |